Assessing Tissue Damage Around a Tape Spring Steerable Needle With Sharp Turn Radii - Omar T. Abdoun; Mark Yim (IEEE Open Journal of Engineering in Medicine and Biology, 2024)
Steerable needles are a novel technology that offers a wide range of uses in medical diagnostics and therapeutics. Currently, there exist several steerable needle designs in the literature, however, they are limited in their use by the number of possible turns, turn radius, and tissue damage. We introduce a novel design of a tape spring steerable needle, capable of multiple turns, that minimizes tissue damage. In this study, we measure the turning radius of our steerable needle in porcine liver tissue in vitro with ultrasound and estimate tissue damage in gel blocks using image analysis and 3D plaster casting. We were able to demonstrate our steerable needle's ability to steer through biological tissue, as well as introduce a novel method for estimating tissue damage. Our findings show that our needle design showed lower damage compared to similar designs in literature, as well as tissue stiffness being a protective factor against tissue damage.